Turning ingroup wounds into bonds: perceptions of gender inequalities predict attitudes toward other minorities - Ciaffoni, Stefano; Rubini, Monica; Moscatelli, Silvia (Frontiers in Psychology, 2024)
Despite significant strides in reducing gender disparities over the past decades, women still face disparities in several domains. While extensive research has explored the various consequences of gender inequalities for women, this study (N = 493 participants) delves into a less-explored dimension, investigating whether and how perceiving gender inequalities is associated with attitudes towards minorities. Drawing on relative deprivation theory and intra-minority solidarity research, we examined the relationship between women's perceptions of gender inequalitiesspanning workplace inequality, domestic inequality, sexual harassment, and social expectationsand attitudes toward gays and lesbians, transgender women, and immigrants. We also explored whether indignation, arising from recognizing unjust circumstances, mediated these relationships, and the moderating role of perceived friends' support for gender equality. The results of the path analyses unveiled a nuanced relationship. While women who were more aware of gender inequalities exhibited more positive attitudes toward gays and lesbians and transgender women, no such relationship was observed regarding immigrants. Indignation and perceived friends' support for gender equality were key factors in fostering positive intergroup attitudes. Regarding their moderating role, perceived social norms only influenced the relationship between indignation and attitudes towards gays and lesbians. These findings shed light on the intricate interplay between gender inequalities and minority group attitudes. Recognizing the multifaceted nature of gender inequality and its emotional impact can catalyze promoting coalitional attitudes and collective action among disadvantaged groups. The study also underscores the potential of close groups' norms in promoting positive intergroup attitudes, warranting further exploration.